The effect of gender in clinically isolated syndrome (CIS): a meta-analysis. - Dobson, R; Ramagopalan, S; Giovannoni, G (2012)
BACKGROUND/OBJECTIVE: A clinically isolated syndrome compatible with demyelination (CIS) is the initial presentation for the majority of people that go on to develop multiple sclerosis (MS). There has previously been little work examining the effect of gender on the development and progression of CIS. METHODS: Data from observational studies of CIS were used. In total, 33 suitable studies with 4732 subjects were identified. RESULTS: The overall relative risk (RR) of CIS in females compared with males was 2.12 (95% CI 1.94-2.32). The RR of females developing MS following CIS was 1.20 (95% CI 0.98-1.46) compared with males. CONCLUSIONS: These data imply that the gender bias seen in MS is caused by factors acting early in the disease process.